Agile practices for global software development vendors in the development of green and sustainable software. Issue 10 (19th June 2018) - Rashid, Nasir; Khan, Siffat Ullah
Abstract: Over the last decade, the use of agile methods has grown dramatically for software development. Agile methods guarantee to accelerate the delivery of remarkable software with increased user satisfaction and reduced cost. However, in recent years, due to emergence of green software engineering, software developers are compelled to focus more on green and sustainable aspects of software. Global software engineering aims to design, develop, and use a software with limited energy and computing resources. Recently, software engineers in global software development (GSD) have adapted agile methods for quick, interactive, and environment‐friendly software development. However, there is a lack of specific practices to be followed by GSD vendors in the development of green and sustainable software. In this study, we have identified 36 agile practices through systematic literature review and applied contrived search criteria derived from the research questions; 53 relevant papers were identified and reviewed. Findings of the systematic literature review were then empirically validated through questionnaire survey in GSD industry, in which 106 relevant experts from 25 different countries participated. The identified agile practices are intended to assist GSD vendors in strengthening their agile maturity towards green and sustainable software development.